PENGARUH METODE PEMBELAJARAN TIPE BUZZ GROUP TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SD INPRES 3/77 WATU KABUPATEN BONE - Hafid, Abd; Mujahidah; Nasir, Nabilah (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This study aims to determine whether there is an effect of the application of the Buzz Group Type Learning Method on the learning outcomes of Indonesian language of grade V students of SD Inpres 3/77 Watu, Bone Regency. This study uses a quantitative approach with a Pre-experimental research type whose design uses One Group Pretest-Posttest. The population in this study were all grade V students of SD Inpres 3/77 Watu as many as 34 students, while the research sample used a saturated sampling population. The research data were obtained using a test instrument. The data analysis technique used was descriptive statistical analysis technique and inferential statistical analysis technique. The results of the study showed that descriptively the average value of the pretest results was 42.50 while the average posttest was 76.85. Based on the results of the inferential analysis, the t count value was obtained (22.726). (>) t table (2.03452) thus H₀ is rejected and H₁ is accepted, it can be concluded that the application of the Buzz Group Type Learning method has a significant effect on the learning outcomes of Indonesian language of grade V students of SD Inpres 3/77 Watu, Bone Regency.